Corrective Rhinoplasty with Combined Use of Autogenous Auricular Cartilage and Porcine Dermal Collagen in Cleft Lip Nose Deformity - Park, Young-Wook (Maxillofac Plast Reconstr Surg, 2014)
Esthetic reconstruction of cleft lip nose deformity is a challenging task in surgical management of patients with orofacial cleft. The author reconstructed cleft lip nose deformity effectively using autogenous auricular cartilage and a relatively new graft material of porcine dermal collagen, Permacol™. After correction of the deformed lower third of the nose with patient’s auricular cartilage, we applied Permacol™ to augment the entire nasal dorsum. Three patients were treated and followed for up to five years. All patients improved in nose aesthetics without any inflammatory or immunogenic reaction. The author suggests that the use of Permacol™ for nasal profile augmentation in the treatment of cleft lip nose deformity is an alternative surgical strategy with minimal surgical invasiveness. The author report long-term experience with combined use of auricular cartilage and Permacol™ in nasal reconstruction for cleft lip nose deformity.